Evaluating civil aviation airport competitiveness in the Yangtze River Economic Belt of China: A lens of spatial-temporal evolution - Zhang, Yang; Jin, Xue; Li, Meng; Liu, Rongtian; Jing, Ying (Frontiers in Environmental Science, 2022)
The civil aviation industry plays an important role of advancing interregional socio-economic development. Investigating the competitiveness of civil aviation airports (CAAs) from the tempo-spatial change perspective aids in the optimization of airport layout towards balanced and coordinated regional development. This research assesses the overall competitiveness and characterizes the spatial-temporal evolution of 86 civil aviation airports in the Yangtze River Economic Belt from 2009 to 2019 by a series of geo-analytical approaches (i.e., entropy weighing, spatial auto-correlation, and Theil index). The findings are concluded: 1) From 2009 to 2019, the overall competitiveness of civil aviation airports is dramatically improved and an evidently hierarchical system is formed at the provincial level, with the spatial pattern of “strong in the east and west, weak in the middle”. 2) The global Moran indexes of civil aviation airport competitiveness in 2009, 2014 and 2019 are negative, indicating that superior and inferior airports are likely to be spatially clustered. 3) The local Moran Indexes show that the spatial agglomeration of civil aviation airport tends to be more evident in the recent decade. The high-high competitiveness clusters lie in the Yangtze River Delta Economic Zone for a long run, transforming from “Shanghai-Hangzhou” high-competitiveness pole to “Shanghai-Hangzhou-Nanjing” and further extends to central Jiangsu. Civil aviation airports in provincial capitals and secondary cities have formed clusters of high-low competitiveness. Moreover, clusters of low-low competitiveness stretch from the Yunnan-Guizhou Plateau to cities in the middle reaches of the Yangtze River. 4) The interprovincial Theil indexes of civil aviation airport competitiveness fluctuate, with the discrepancy increasing and then decreasing.